Sistem Pendukung Keputusan Dalam Pemilihan Ketua Jurusan Dengan Metode Vikor Pada Sekolah Menengah Kejuruan(SMK) Swasta Budisatrya Medan - Herni Herni (STMIK Budi Darma, 2021)
In the selection of department heads, elections are held once a year, namely every new academic year. Constraints or problems that occur in the selection of department heads are when the data collection process for prospective department heads only determines the criteria. While the requirements to become head of the department are not carried out. So that the selection of the head of the department is not optimal or efficient. With a computerized decision support system for selecting department heads, it can make it easier for us to make decisions, so that it can produce more accurate information than before. In addition, the criteria set must also be more varied and complete so that the selection of the head of the department is not bound by education and years of service but must also be supported by the personality and competence of the candidate for the head of the department. The solution was carried out in the selection of department heads to facilitate the process of selecting department heads at SMK Budisatrya Medan. so as to get optimal results in the election of the chairman of the Budisatrya Medan Vocational School. With a computerized decision support system for selecting department heads, it can make it easier for us to make decisions, so that it can produce more accurate information than before